1991
DOI: 10.1002/eji.1830210218
|View full text |Cite
|
Sign up to set email alerts
|

Selective migration of the human helper‐inducer memory T cell subset: confirmation by in vivo cellular kinetic studies

Abstract: The vast majority of T cells present in chronic inflammatory lesions are of the helper-inducer/memory (CD45RO+CD29+) phenotype; suppressor-inducer/naive cells (CD45RA+) are virtually absent. Furthermore, CD4+ T cells are found more frequently than CD8+ cells. Previous in vitro studies have suggested that this may be, in part, due to the increased capacity of CD45RO+CD29+ T cells to bind to endothelium and, thus, enter inflammatory foci but no in vivo evidence for preferential migration exists. To investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 34 publications
5
53
0
Order By: Relevance
“…In this model (29), mild suction is used to elicit blister formation at the dermo-epidermal junction following intradermal injection with treponemal lipopeptides. In contrast with the paucity of cells in fluid from blisters raised over salineinjected skin or unmanipulated normal skin, fluid within blisters elicited over sites of inflammation contains numerous extravasated immune cells that can be analyzed by flow cytometry (30 -33); comparison with peripheral blood (PB) enables one to identify selectively recruited leukocyte subsets and to assess the influence of the inflammatory microenvironment on their state of activation/ differentiation (31)(32)(33). There is now extensive evidence that the composition of cells in blister fluid accurately reflects the cellular infiltrates within the underlying dermis (30 -33).…”
Section: The Cutaneous Response In Humans Tomentioning
confidence: 99%
“…In this model (29), mild suction is used to elicit blister formation at the dermo-epidermal junction following intradermal injection with treponemal lipopeptides. In contrast with the paucity of cells in fluid from blisters raised over salineinjected skin or unmanipulated normal skin, fluid within blisters elicited over sites of inflammation contains numerous extravasated immune cells that can be analyzed by flow cytometry (30 -33); comparison with peripheral blood (PB) enables one to identify selectively recruited leukocyte subsets and to assess the influence of the inflammatory microenvironment on their state of activation/ differentiation (31)(32)(33). There is now extensive evidence that the composition of cells in blister fluid accurately reflects the cellular infiltrates within the underlying dermis (30 -33).…”
Section: The Cutaneous Response In Humans Tomentioning
confidence: 99%
“…Almost all synovial T cells are primed, expressing high levels of an isoform of the leukocyte common antigen termed CD45RO (5,6). Primed and activated T cells appear to enter the joint in a nonspecific manner because of their high level of expression of adhesion molecules (7). The strongly biased population that results is very likely to have a different pattern of activity compared with unselected peripheral blood cells (2).…”
mentioning
confidence: 99%
“…Others have observed later expression of the memory cell phenotype by the vast majority of PHA-stimulated T cells from healthy individuals [11,13,14], Changes were not due to increased cell proliferation, and consistent with this, conversion into the memory cell phenotype has not been found to be necessarily correlated with proliferation [31], Increased expression of adhesion molecules might lead to facilitated localization of memory T cells to the inflamed tissue [32], In this regard, Pitzalis et al [33] have demonstrated the preponderance of CD4+CD29+UCHL1 + cells in the rheumatic joint, and in other inflammatory lesions [34], In addition, CD29+ memory T cells have been shown to have a greater ability to adhere to vascular endothelium than their CD29c ounterpart [35], Therefore, enhanced expression of CD29 and other adhesion molecules might lead to accumulation of CD4+ memory cells at tissue sites, and could result in depletion ofthis cell subset in the peripheral blood of patients with MCTD, Interestingly, activated T cells and a high proportion of CD4+ cells have been detected in the infiltrated skin of PSS patients with recent onset of disease [36], It remains to be clarified whether the imbalance of CD4+ cell subsets might lead to reduced suppressor T cell function in patients with MCTD, Similar to Melendro et al [7], we observed diminished numbers of CD8+ cells in MCTD, Data obtained earlier by Alarcjon-Segovia & Ruiz-Arguelles [6] suggest that anti-RNP antibodies might cause deletion of suppressor T cells. It might be considered that altered responsiveness and lymphokine secretion of CD4+ cell subsets exert indirect effects on CDS"*" cells by enhancing B cell activity.…”
Section: Discussionmentioning
confidence: 82%